Expression Strategy of Aedes albopictus Densovirus - Pham, Hanh T. (American Society for Microbiology, 2013)
The transcription map of the Aedes albopictus densovirus (AalDNV) brevidensovirus was identified by Northern blotting, rapid amplification of cDNA ends (RACE) analysis, and RNase protection assays. AalDNV produced mRNAs of 3,359 (NS1), 3,345 (NS2), and 1,246 (VP) nucleotides. The two overlapping P7/7.4 NS promoters employed closely located alternate transcription initiation sites, positioned at either side of the NS1 initiation codon. All NS mRNAs coterminated with VP mRNA. All promoters, explored using luciferase assays, were functional in insect and human cell lines.